Classification statistique et hydrochimique des eaux souterraines de la plaine d'El-Outaya. (W) de Biskra. Algérie. Mars 2011, . - Brinis Nafaa; Boudoukha Abderahmane (Publication au courrier du savoir, Univ-Biskra, 2011)
The plain of El-Outaya is in arid zone in southern Algeria. The groundwater are characterized by an Important and variability in its salinity. This work is presented to improve knowledge on these waters by proceeding to their statistical and hydrochemical classifications. Method C.A.H (hierarchical ascending classification) takes of three tendencies based on the importance of the mineralization. The salt rocks are responsible of this height salinity. Concerning the hydrochemical synthesis, the statistical information is confirmed. There is three dominant groups.